Characteristics of Slum Housing at TPA Suwung - Putu Putri Puspita Dewi Sura, Ni; Ketut Ayu Siwalatri, Ni; Putu Sueca, Ngakan (Universitas Ibn Khaldun Bogor, 2022)
Economic development in urban areas indirectly changes the function of residential areas into commercial areas. Along with the development of the function of the Gajah Mada area, the threat of decreasing the visual quality of Jalan Gajah Mada as an artifact of the corridors of the Denpasar Old Town area naturally cannot be avoided. The need for increased trading space, high building density, development of economic functions that are more commercial in nature due to the demands of profit and modernization as well as a slum environment can also eliminate the visual character of the physical corridor of Jalan Gajah Mada which still retains the characteristics of Balinese architecture and the image of Kota Tua because Therefore, it is necessary to study the visual characteristics of the physical corridors of Jalan Gajah Mada so that directions regarding the arrangement should be considered in accommodating changes in the physical corridors so that they remain visually aligned. This research method is a type of descriptive research using qualitative methods. Descriptive research is a research that aims to provide a systematic, factual, accurate description of the facts and characteristics of the population so that it can produce the physical characteristics of the Jalan Gajah Mada corridor as seen from the path elements, architectural patterns and street trees that surround the corridor.